METASOMATIC ALTERATIONS IN FERROMAGNESIAN ECLOGITE FROM THE UDACHNAYA PIPE - Solov'yeva L.V.; Barankevich V.G.; Zav'yalova L.L.; Lipskaya V.I. (My University, 1988)
Earlier we described examples of so-called late metasomatic alteration in ultramafic inclusions from the Udachnaya pipe. The chemical composition of superposed amphibole, titanium phlogopite, aluminum spinel and djerfisherite suggests that solid bimineralic eclogite material interacted with fluid carrying S, Cl, F, H2O, CO2 and α/α-group elements. Before getting into the kimberlite melt, the eclogite material evidently had gone past a presumed magmatic stage of primary garnet and clinopyroxene crystallization, as well as a stage of mantle metasomatism. One consequence of such metasomatism could be a too-high Nd-Sm age of some eclogites, obtained by the isochron method on garnet and clinopyroxene.